EVALUASI KEBIJAKAN PENANGKARAN BUAYA BINAAN BALAI KONSERVASI SUMBER DAYA ALAM SULAWESI TENGAH - Christin, Vernanda; Kurnia, Intam; Nasrullah, Nasrullah (CV. Lafadz Jaya, 2025)
Evaluation of the Crocodile Breeding Policy under the auspices of the Central Sulawesi Natural Resources Conservation Agency aims to assess the success and effectiveness of this policy in managing crocodile breeding, as well as its impact on wildlife conservation and community welfare. This study uses a qualitative descriptive method with primary and secondary data collected through interviews, observations, and documentation. Data were obtained from the Central Sulawesi Natural Resources Conservation Agency, breeding partners PT. Mas Indah Permai, and the surrounding community. The analysis was conducted using William N. Dunn's policy evaluation theory, with six indicators: effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The results of the study indicate that this crocodile breeding policy is not yet fully optimal. The effectiveness indicator shows that although this program is running well in helping to handle crocodiles, obstacles such as lack of infrastructure and financing still hinder the achievement of objectives. The efficiency and adequacy indicators also show imperfections, especially in terms of the budget and facilities needed. Overall, this program has made a positive contribution to conservation, but still requires improvements in the aspects of regulation and financial support. This study suggests the need to improve policies, regional regulations, and support for breeding partners so that conservation objectives can be achieved more optimally.